Exploratory study on the preparation of guidelines for the analysis of graphs in corporate performance reporting - Eng, Wan Lung (2008)
The use of graphs in corporate reports has been extensive, but many of these graphs are found to be distorted and misleading. This study attempts to expand on existing literature and develop a set of metrics to measure the degree of misrepresentation in graphical design and construction.